2015
DOI: 10.1039/c5ce00474h
|View full text |Cite
|
Sign up to set email alerts
|

Controlled synthesis of gold nanorings with structural defects assisted by elastic induction of mixed surfactants

Abstract: Controlled synthesis of gold nanorings was realized by reducing chloroauric acid in aqueous mixed solutions of cetyltrimethyl ammonium bromide (CTAB) and sodium dodecyl sulfate (SDS). It is revealed that the gold nanowires are induced to fabricate the gold nanorings with an average diameter of ~300 nm. The synthesis of the nanowires and the formation of the nanorings can be achieved in one step. A variety of gold nanostructures, such as short nanowires, nanorings, nanostars with a number of soft protuberances … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…34 The size transition of SDS:CTAB templates from nanoscale to micrometer-scale and the binary capping effect upon temperature change may exert a subtle impact on the overall capping process, resulting in a difference in the gold growth direction and increasing the diversity of the gold structures that are grown. 9,27,32 Additionally, we found that vigorous mechanical stirring is critical to ensure the complete closure of the gold loop. Experiments carried out in static conditions (no magnetic stirring) revealed a majority of unclosed toroidal structures (Figure S6).…”
Section: Acs Applied Nano Materialsmentioning
confidence: 87%
See 4 more Smart Citations
“…34 The size transition of SDS:CTAB templates from nanoscale to micrometer-scale and the binary capping effect upon temperature change may exert a subtle impact on the overall capping process, resulting in a difference in the gold growth direction and increasing the diversity of the gold structures that are grown. 9,27,32 Additionally, we found that vigorous mechanical stirring is critical to ensure the complete closure of the gold loop. Experiments carried out in static conditions (no magnetic stirring) revealed a majority of unclosed toroidal structures (Figure S6).…”
Section: Acs Applied Nano Materialsmentioning
confidence: 87%
“…Although two-dimensional (2D) metal nanoring arrays produced by lithography-based processes enable great control over the periodic arrangement of the nanoring, the underlying support greatly reduces the effective surface area compared to freely floating nanorings, resulting in limited applications for biomedical research. Lithographic techniques also usually suffer from a complicated, time-consuming fabrication process with low yield and a dependence on expensive facilities. , Wet chemistry provides a direct and facile approach for nanoring synthesis. , Jiang et al reported an ultrasonic irradiation assisted aqueous synthesis of gold nanorings which had a reduced reaction time and a stable reaction condition ascribed to the Ostwald ripening process . However, since the gold nanorings were produced from oxidizing a silver nanotemplate, additional purification steps were needed to remove the AgCl impurity.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations